Strategi Pemulihan Ketahanan Pangan Pascabencana Melalui Hortikultura dan Hidroponik di Pekarangan Rumah - Mualfah, Desti; Herlina, Nofripa; Fitriana, Nur; Wati, Anisa Dwi Sanggar (LPPM UMRI, 2026)
Agam Regency, West Sumatra, is an area with a high level of vulnerability to hydrometeorological disasters, including flash floods that have an impact on reducing household food security. After the disaster, the community of Sungai Batang Village faced limited access to healthy food, damaged agricultural land, and low utilization of yards as alternative food sources. This community service activity aims to improve household food security through the utilization of backyard horticulture and simple hydroponics based on community empowerment. The methods used were participatory and collaborative approaches through the stages of socialization, initial identification and assessment, participatory planning, technical training, application of horticulture and hydroponics technology, assistance and monitoring, and activity evaluation. The results of the activity showed an increase in community skills in vegetable cultivation, as well as an increase in productive home gardens and active hydroponics units. This program also strengthened the social participation of the Dasawisma and Karang Taruna groups and encouraged household-scale economic independence. Thus, the simple yard horticulture and hydroponic model is the most appropriate solution as a strategy for restoring food security after a disaster.